AKIBAT HUKUM PEMBATALAN KERJASAMA ANTARA PROMOTOR KONSER DENGAN ARTIS AKIBAT PANDEMI COVID-19 - Mohammad Dipa Fahmi Lazuardi; Rosalinda Elsina Latumahina (Gapenas Publisher, 2023)
A music concert event is currently one of the community's sources of entertainment. Because a music event allows followers of a singer and/or band, both local and worldwide performers, to see their idols live. Furthermore, the atmosphere of a music concert can undoubtedly create an impression and experience for the audience. A music performance event will never be devoid of admirers due to the interdependence of these components. Another factor supporting the continued existence of music concerts is the growing public desire for music. The various music performances held in both festival and tour styles, both in Indonesia and abroad, demonstrate the vibrancy of a musical performance. Similarly, there is a high level of public interest in purchasing musical tickets. Every time a music event is held, hundreds or even tens of thousands of people pack the venue. Due to overwhelming demand from the public, promoters frequently lengthen the time of music concerts. One essential factor driving the music industry's rapid expansion is the preservation of solid cooperative relationships between concert promoters and performers.